PENERAPAN STRATEGI PEMBELAJARAN SCAFFOLDING PADA MATERI GELOMBANG BUNYI DAN CAHAYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI DI MAN 1 INHIL - Atika Nurul Fathiyah; Mitri Irianti; Azizahwati Azizahwati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study was aimed to determine the enhancement of student learning result in physics by the aplication of scaffolding learning strategy. The type of reseach which was used was quasi experiment with nonequivalent control group design. The population in this study was the students of XI IPA class at MAN 1 INHIL academic year 2017/2018 which consisted of 123 student divided in four classes. The sample in this study was obtained based on the normality and homogenity tests. When all of classes were proved to be normal and homogenous, two classes were chosen randomly to be the experiment class and control class. The instrument which was use to collect the data was a test of learning result as pretest and posttest. The data was analize by the descriptive and inferential analysis. Descriptive analysis showed the avarage absorption level in experimen class was 80,22 % and 70,22 % for control class, both were in good category. Based on the inferential analysis, it can be concluded that the application of scaffolding learning strategy can enhance students’ study result at XI IPA 1 class of MAN I INHIL on sound and light waves material.Keywords : Scaffolding learning strategy, study result, sound and light waves.